Environmental vibration reduction utilizing an array of mass scatterers. (2017) - Peplow, A.T.; Andersen, L.V.; Bucinskas, P.
Abstract: Ground vibration generated by rail and road traffic is a major source of environmental noise and vibration pollution in the low-frequency range. A promising and cost effective mitigation method can be the use of heavy masses placed as an array on the ground surface near the road or track (e.g. concrete or stone blocks, specially designed brick walls, etc.). This work concerns the effectiveness of such "blocking" masses. A semi-analytical lumped-parameter method is utilized, assuming that the blocks are point masses situated on an elastic half-space. The work is enhanced by examples highlighting advantages and disadvantages of single-mass scatterers and multiple-mass scatterers.